HAZ effects in hot-rolled dual-phase steel during flash butt welding of wheel rims - Han, Jian; Zhu, Lisong; Wang, Jun; Zhang, Caidong; Sun, Li; Zhang, Zhigiang; Ma, Cheng; Jiang, Zhengyi; Linton, Valerie (Springer, 2023)
The embrittlement and softening behavior in simulated heat-affected zones (HAZ) of a newly designed dual-phase DP680 steel for wheel rim applications with different flash allowances were investigated to determine weldability, and offer valuable information for the steel design and its subsequent flash butt welding (FBW). The characterization of microstructure and mechanical performance for the simulated HAZ was conducted by means of optical microscopy, scanning electron microscopy, electron backscatter diffraction, hardness distribution, and Charpy V-notch (CVN) values at selected temperatures. The investigation demonstrates that the toughness of coarse-grained HAZ was kept at an average level of 25.3 J when the prior austenite grain size was controlled to 60.54 μm at a flash allowance of 14 mm (equivalent to heat input of 15.14 kJ/cm based on real welding process), which exhibits the worst toughness when the flash allowance was changed from 4 to 14 mm. Further, with a higher martensite fraction (> 30 pct) in base material (BM), the softening occurs in inter-critical HAZ (ICHAZ) instead of sub-critical HAZ since most of martensite in ICHAZ has decomposed, and the rest ferrite and newly formed bainite with remaining martensite reduce the hardness to a larger extent compared to SCHAZ, whose martensite has only partly decomposed. Even if the softening degree is up to 21.6 pct compared to the BM (average 233 HV0.5), the work hardening during a series of forming processes after FBW has alleviated the softening evidently (work hardening degree > 10 pct). However, the failure location is still in ICHAZ after forming extension which has been confirmed in practical applications of DP680 FBW and subsequent forming processes.